Assessing Community Leadership: Understanding Community Capacity for Health Improvement. (July 2017) - Castle, Billie; Wendel, Monica; Kelly Pryor, Brandy N.; Ingram, Monique
Abstract : Objective: The purpose of this study was to pilot a quantitative instrument to measure aspects of community leadership within an assessment framework. Design: The instrument includes 14 Likert-type questions asking residents how they perceive leaders within 5 sectors: Louisville Metro Council/Mayor's Office, the faith community, education, business, and the civic sector. Setting: Louisville/Jefferson County, Kentucky, has a population of about 743 000 residents. Respondents were asked to examine leadership within West Louisville, an economically deprived area of the city made up of 9 contiguous neighborhoods. This area is predominantly African American (78% compared with 22% in Louisville Metro), with an overall poverty rate of 43% (compared with 18% in Louisville Metro), and unemployment rate of 23% (compared with 8% in Louisville Metro). Residents of West Louisville are looking to leadership to address many of the inequities. Participants: Twenty-seven participants representing 7 community sectors completed the survey, of whom 90% work in West Louisville. Main Outcome Measure(s): The instrument measured local perceptions of leadership strength, effectiveness, trust, communication, community building, and leadership development. Results: The majority of respondents agree that strong leadership exists across the 5 sectors, with variation regarding perceptions of the quality of that leadership. City leadership within the Mayor's Office and Metro Council is largely viewed positively, while the growing tensions within the education sector were reflected in the survey results. Conclusion: The perception of community leadership is important to understanding local community capacity to improve health and also inclusivity of community voice in the assessment and community improvement processes. Results from such assessments can offer useful information for strengthening community capacity and sustaining relationships needed to enact progressive and equitable solutions to address local issues. Leaders in a variety of settings can utilize this instrument to improve their community as well as their practical approaches towards leadership and equity.